Bacterial vaginosis in Tribhuvan University Teaching Hospital - Manandhar, R.; Sharma, J.; Pokharel, B.M.; Shrestha, B.; Pradhan, N. (Journal of Institute of Medicine Nepal, 2007)
Five hundred women of reproductive age group were screened for bacterial vaginosis (BV) using Amsel’s criteria from January 2004 to July 2004 at gynaecological out patient department of Tribhuvan University Teaching Hospital (TUTH). Bacterial vaginosis was found in 2.5%. Among all BV positive patients, 67.3% were symptomatic and 32.7% were asymptomatic. Brahmans were significantly least infected caste. Highly educated women were also significantly least infected group. Sexual exposure has significant association with BV. Smokers and people using alcohol suffered much from bacterial vaginosis but were not statistically significant. Journal of Institute of Medicine Vol.27(2) 2005